Scientific justification for the specific application of ESG principles - Adambekova, A.; Adambekov, N.; Amankeldy, N.; Salimbayeva, R. (Journal of Economic Research & Business Administration, 2023)
Achieving sustainable development goals, designated by the UN as a key vector of the world order, has become an important guideline in the development of public administration and big business in recent years. The study is aimed at studying features that take into account the results of world research and reflect real trends in the study of problems of achieving sustainable development goals. The research was carried out in several stages: a literature review, identifying patterns and trends in ESG research and conducting a bibliometric analysis based on it. Also, there were studied main prerequisites for the development of ESG principles and ESG reporting, and the regulations accompanying their formation, as well as the current approaches of international organizations in promoting commitment to sustainable development goals. Descriptive types of research (comparison, critical review, argumentation, etc.) are used in the article to review research on ESG practices taking into account global trends. The research covers the period from 2010 to 2023. The results show that the development of National Sustainable Development Standards is not sufficient to create conditions for promoting ESG culture in society. The need for regulations, systemic reporting and ESG reporting methodology, an informal approach to the very commitment of business to ESG on an integrated and systematic basis is justified by a review of the results of advanced and relevant researches on ESG issues. The article is valuable for top managers and executives of organizations, state and local government bodies, as well as researchers interested in promoting the concept of commitment to sustainable development and ESG goals for business. Key words: ESG principles, sustainable development goals, bibliometric analysis, international organizations.